The gridlock economy : how too much ownership wrecks markets, stops innovation, and costs lives - Heller, Michael, 1962- (Basic Books, 2008)
25 new runways would eliminate most air travel delays in America. Why can't we build them? 50 patent owners are blocking a major drug maker from creating a cancer cure. Why won't they get out of the way? 90% of our broadcast spectrum sits idle while American cell phone service lags far behind Japan's and Korea's. Why are we wasting our airwaves? 98% of African American-owned farms have been sold off over the last century. Why can't we stop the loss? All these problems are really the same problem-one whose solution would jump-start innovation, release trillions in productivity, and help revive.